METAFORA DALAM KUMPULAN PUISI MATA PEMBURU KARYA MAHDI IDRIS - Samhudi, Samhudi (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
This research describes the form of metaphor in the poetry collection Mata Pengburu by Mahdi Idris. The research method used is descriptive qualitative. The data source in this research is the poetry collection Mata Pengburu by Mahdi Idris. The data used is an array containing metaphors in the poetry collection Mata Pengburu by Mahdi Idris. The technique for collecting data is using reading techniques and note-taking techniques by marking parts of the lines containing metaphors in the poetry collection Eye of the Hunter by Mahdi Idris. The research results show that there are four forms of metaphor in the poetry collection Mata Pengburu by Mahdi Idris, namely anthropomorphic metaphor, animal metaphor, concrete to abstract metaphor, and synaesthetic metaphor. Researchers found 44 data contained in the poetry collection Mata Pengburu by Mahdi Idris regarding metaphor forms which were grouped into 4 sections, namely 29 anthropomorphic metaphor data, 7 animal metaphor data, 7 concrete to abstract metaphor data, and 1 synaesthetic metaphor data. Of the four metaphors, anthropomorphic metaphors often appear in the poetry collection Mata Pengburu by Mahdi Idris.